2010
DOI: 10.1242/jeb.039768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of static magnetic fields on the development and aging ofCaenorhabditis elegans

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
1
10
1
Order By: Relevance
“…In contrast, our data demonstrated that timing and rate of development from eggs to adults were delayed by embryonic exposure to 8.5 T SMF. One possible explanation for differences between our present work and previous findings is intensity and duration of exposure to magnetic fields [Hung et al, 2010]. Experimental variables such as sample insertion speed and gradient currents should be considered in future studies.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In contrast, our data demonstrated that timing and rate of development from eggs to adults were delayed by embryonic exposure to 8.5 T SMF. One possible explanation for differences between our present work and previous findings is intensity and duration of exposure to magnetic fields [Hung et al, 2010]. Experimental variables such as sample insertion speed and gradient currents should be considered in future studies.…”
Section: Discussioncontrasting
confidence: 78%
“…Although clinical MR systems using SMFs up to 8 T have been considered a``non-significant risk'' to adult patients by the Center of Device and Radiological Health [FDA, 2003], a number of recent studies indicated that SMFs may affect early embryonic development. Exposure to 200 mT SMF was reported to shorten the lifespan of C. elegans, but their development rate was accelerated, and expression of genes associated with development and aging pathways such as clock (biological timing) abnormality-1 (clk-1), LIM domain family (lim-7), abnormal cell lineage-4 (lin-4), uncoordinated-3 (un-3), aging alteration-1 (age-1), and daf-2, was altered at the mRNA level [Hung et al, 2010]. In contrast, our data demonstrated that timing and rate of development from eggs to adults were delayed by embryonic exposure to 8.5 T SMF.…”
Section: Discussionmentioning
confidence: 99%
“…(Bowling 2007;Glass 2003;Hung, Lee, Chen, and Huang 2010;Pruchno, Wilson-Genderson, and Cartwright 2010;Pruchno, Wilson-Genderson, Rose, and Cartwright 2010) For example, Rowe and Kahn’s model of successful aging, (Rowe and Kahn 1997) one of the most widely accepted and applied models,(Dillaway and Byrnes 2009) views “better than average” aging as a combination of three components: avoiding disease and disability, high cognitive and physical function, and engagement with life. Recent models continue to support the multidimensional nature of this construct and have incorporated both objective and subjective dimensions in their definitions of successful aging.…”
Section: Introductionmentioning
confidence: 99%
“…Besides alternating magnetic fields, static magnetic fields also can affect the locomotion and lifespan in C. elegans. Hung et al reported reduced crawling speeds when worms were exposed to static magnetic fields [24] [25]. Investigations regarding the directional ability of worms in magnetic fields have been less conclusive.…”
Section: Introductionmentioning
confidence: 99%